70.6k views
4 votes
A=

B=
G(x) is a transformation of f(x) can you explain how I would get what A and B are?

A= B= G(x) is a transformation of f(x) can you explain how I would get what A and-example-1
User Espo
by
4.1k points

1 Answer

3 votes

Answer:
A=1, B=-2

Explanation:

The endpoints changed from -1 and 2 to -4 and 2, so B = -2.

We know the points (-1, -1) and (2, -1) correspond, so A = 1.

A= B= G(x) is a transformation of f(x) can you explain how I would get what A and-example-1
User Riyaz
by
4.3k points